2020
DOI: 10.1021/jacs.9b09808
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Sequencing of an Expanded Genetic Alphabet Reveals High-Fidelity Replication of a Predominantly Hydrophobic Unnatural Base Pair

Abstract: Unnatural base pairs (UBPs) have been developed and used for a variety of in vitro applications, as well as for the engineering of semi-synthetic organisms (SSOs) that store and retrieve increased information. However, these applications are limited by the availability of methods to rapidly and accurately determine the sequence of unnatural DNA. Here, we report the development and application of the MspA nanopore to sequence DNA containing the dTPT3-dNaM UBP. Analysis of two sequence contexts reveals that DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Our thermal stability analysis demonstrates that the most stable unnatural mispairs are with dA, likely due to the greater hydrophobicity and size of adenine compared to the other natural nucleobases (See Figure S3 in the Supporting Information). The most frequent substitution mutation observed in vivo is dNaM mutated to dT [19,33] . Therefore, dNaM‐>dT mutations could arise via stable dNaM:dA mispairs, where the incorrectly synthesized adenine is replicated, replacing dNaM with thymine in future rounds of replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our thermal stability analysis demonstrates that the most stable unnatural mispairs are with dA, likely due to the greater hydrophobicity and size of adenine compared to the other natural nucleobases (See Figure S3 in the Supporting Information). The most frequent substitution mutation observed in vivo is dNaM mutated to dT [19,33] . Therefore, dNaM‐>dT mutations could arise via stable dNaM:dA mispairs, where the incorrectly synthesized adenine is replicated, replacing dNaM with thymine in future rounds of replication.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dNaM‐>dT mutations could arise via stable dNaM:dA mispairs, where the incorrectly synthesized adenine is replicated, replacing dNaM with thymine in future rounds of replication. Even though dNaM self‐pairing is nearly as thermally stable as the dNaM:dTPT3 heteropair, nanopore sequencing of PCR and in vivo replicated unnatural DNAs demonstrate that unnatural self‐pairs are rarely propagated [33] . Therefore, selectivity for heteropair formation is imparted predominantly by polymerases where pairing structure conformations may contribute to maintenance of proper UBP orientation [34] …”
Section: Discussionmentioning
confidence: 99%
“…However, ϕ29 DNA polymerase may be employed in this instance as it exhibits reverse transcriptase activity when encountering the FANA template [139]. Recent work has shown that MspA can be used to sequence DNA containing the dTPT3-dNaM unnatural base pairs [141] ( Figure 6). CsgG may be another suitable pore for the detection of unnatural nucleotides, as the MinION setup has been shown to distinguish between 11 different thymidine analogs [142].…”
Section: Detection Of Nucleic Acidsmentioning
confidence: 99%
“…Additionally, this finite read length still represents a significant improvement over the small size of fragments used in mass spectrometry or Edman degradation, and protein fragmentation and shotgun sequencing methods similar to those used in traditional protein sequencing can naturally be applied to this new technique. Technical modifications such as using a variable-voltage control scheme ( 29, 35 ) have been shown to significantly improve the accuracy of DNA sequencing, and the physical principle of this is equally applicable to peptide sequencing (Supplementary Note 9).…”
Section: Figurementioning
confidence: 99%